Influência da eficiência no uso da água e energia no custo do ciclo de vida de uma moradia multifamiliar popular em Belo Horizonte - Brasil - Tatiane Candida do Nascimento (2010)
The implementation of sustainable actions in a building often encounter obstacles for the enterprising and / or customer because the analysis for decision making is counted only the costs of implementing such measures, without considering their impact over the cycle life of the enterprise. The method of life cycle cost analysis of a product is an important tool that demonstrates the economic viability of a product considering the manufacture, usage and disposal. Thus the analysis of the costs of the life cycle of a building would include not only the initial costs, but also the future costs related to the operation, maintenance, and deactivation of the enterprise. This paper uses the method of costanalysis of the life cycle to justify the implementation of sustainable measures in popular housing. The results indicate to taking a look at the life of an enterprise considering beyond the initial investment all the major costs incurred throughout its life cycle, enables more sustainable buildings not only as a selling point, but as good business, so to increase their profitability. It is intended also to call attention to investors and developers to the need of creating a new culture that considers the possible gains from cost analysis life cycle, so that projects containing measures to make the sustainable buildings can be seen as viable and interesting in a marketing viewpoint.